Occult Uterine Sarcoma and Leiomyosarcoma: Incidence of and Survival Associated With Morcellation. Issue 1 (January 2016) - Raine-Bennett, Tina; Tucker, Lue-Yen; Zaritsky, Eve; Littell, Ramey D.; Palen, Ted; Neugebauer, Romain; Axtell, Allison; Schultze, Peter M.; Kronbach, David W.; Embry-Schubert, Julia; Sundang, Alvina; Bischoff, Kimberly; et al.
Abstract : OBJECTIVE: To estimate the incidence of occult uterine sarcoma and leiomyosarcoma in hysterectomies for leiomyomas and the risk associated with their morcellation. METHODS: We conducted a population-based cohort study. All uterine sarcomas from 2006–2013 in an integrated health care system were identified. Age- and race-specific incidences of occult uterine sarcoma were calculated. Kaplan-Meier survival analysis was performed. Crude and adjusted risk ratios of recurrence and death associated with morcellation at 1, 2, and 3 years were estimated using Poisson regression with inverse probability weighting. RESULTS: There were 125 hysterectomies with occult uterine sarcomas identified among 34, 728 hysterectomies performed for leiomyomas. The incidence of occult uterine sarcoma and leiomyosarcoma was 1 of 278 or 3.60 (95% confidence interval [CI] 2.97–4.23) and 1 of 429 or 2.33 (95% CI 1.83–2.84) per 1, 000 hysterectomies. For stage I leiomyosarcoma (n=111), eight (7.2%) were power and 27 (24.3%) nonpower-morcellated. The unadjusted 3-year probability of disease-free survival for no morcellation, power and nonpower morcellation was 0.54, 0.19, and 0.51, respectively ( P =.15); overall survival was 0.64, 0.75, and 0.68, respectively ( P =.97). None of the adjusted risk ratios for recurrence or death were significant except for death at 1 year for power and nonpower morcellation groups combined (6/33) compared with no morcellation (4/76) (5.12, 95% CI 1.33–19.76, P =.02). We had inadequate power to infer differences for all other comparisons including 3-year survival and power morcellation. CONCLUSION: Morcellation is associated with decreased early survival of women with occult leiomyosarcomas. We could not accurately assess associations between power morcellation and 3-year survival as a result of small numbers. Abstract : Morcellation is associated with decreased early survival of women with occult leiomyosarcomas.